ANALISIS TEMPERATUR DAN TONASE DALAM PENENTUAN OIL LOSSES CPKO PADA INDUSTRI PENGOLAHAN MINYAK: Analysis of Temperature and Tonnage in Determining CPKO Oil Losses in the Oil Processing Industry - Rizki Fadhillah Lubis; Ari Pranata Primisa Purba; Silvi Armaini (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2022)
Oil losses in the oil processing industry is still of particular concern. The purpose of this study is to find out how the relationship and influence between CPKO oil tonnage and temperature in each tank, analyze oil losses and causal factors using Correlation and Linear Regression. Based on the results of research it can be known that there is a suspected relationship between temperature and oil tonnage. There are several factors that cause oil losses including human error and other factors such as the condition of the tank, raw materials and the monitoring process. Recommended improvement proposals for the company are to improve the method of sounding, equip the tank with temperature monitoring, refine sounding equipment, supervise operators in the work area and conduct supervision for each receipt of raw materials.